Peacemaking in Africa : - a critical analysis of the relationship between the African Union and African sub-regional organizations in recent peacemaking initiatives - Ancas, Sarah (Department of Political Studies, 2014)
This thesis considers the question of how, in practice, a regional organization comes to take the leading role in managing a peacemaking intervention. More specifically, it considers which criteria, if any, are used in the choice of a lead actor in peacemaking efforts, and how the principles of 'subsidiarity, complementarity and comparative advantage,' as laid out in the Memorandum of Understanding between the AU and the subregional organizations, are being applied in this decision making. The recent example cases of Zimbabwe, Kenya and Cote d'Ivoire are specifically analyzed to show the reality of the working relationship in the present.